Character Design of Eren Yeager in Animated Attack on Titan Series from Season 1-4 - D F Rosyid; R Maulina (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Attack on Titan is a popular animated series from japan that was adapted from a comic book with the same title created by Hajime Isayama, this animated series is set in a fictional world where humans live surrounded by a huge wall that protects them from giant man-eating creatures called titans. The main character in this series is Eren Yeager, a young man who can be a “titan shifter”. which is an ability to transform into a titan creature. One of the factors that influence the popularity of Attack on Titan is the visualization of the main character Eren Yeager, and his character in each season, making him an interesting and strong character to be discussed. This study was conducted to describe the development of the main character design from season 1 to season 4. The method is used to visually describe the character and personality built by the author. it’s hoped that this research can be used as reference material in making a fictional character design for future needs.